THE APPLICATION OF HABEAS CORPUS 143.641 OF THE SUPREME FEDERAL COURT FROM A GENDER PERSPECTIVE: A QUALITATIVE ANALYSIS FROM TJ/SP DECISIONS (Revista Paradigma, 2023)
The purpose of this article is to analyze the presence of gender stereotypes in decisions that applied the Collective Habeas Corpus nº 143.641, judged by the 2nd Panel of the Supreme Federal Court (SFC). The writ deals with the substitution of preventive prison for home prison for pregnant women and/or mothers of children under 12 / deficient, as long as they are not accused of crimes involving violence or serious threats/against their offspring and except in exceptional situations. The research is empirical, of a qualitative nature and based on data obtained by analysis of judicial processes, more specifically, of judgments of the Court of Justice of São Paulo that deal with the theme. From the results found, it was possible to identify the reproduction of gender stereotypes in court decisions, which negatively affected the effectiveness of the right granted, despite the fulfillment of the requirements previously stipulated by the SFC. The research collaborates, therefore, with the construction of empirical evidence related to barriers to access to justice for women resulting from the use of gender stereotypes in judicial decisions.
Keywords: Gender Stereotype. Maternity. Home prison. Judicial Decision. Collective Habeas Corpus nº 143.641